2020
DOI: 10.1002/jmv.25962
|View full text |Cite
|
Sign up to set email alerts
|

Development of a sensitive and specific nanoparticle‐assisted PCR assay for detecting HPV‐16 and HPV‐18 DNA

Abstract: Carcinoma precursor lesion caused by persistent infection of human papillomavirus (HPV) types 16 and 18 is known as a principal inducer of cervical cancer. Therefore, rapid and effective detection of HPV‐16 and HPV‐18 infection at early stage is an important strategy for preventing such disease. In this study, a novel duplex nanoparticle‐assisted polymerase chain reaction (nanoPCR) assay was developed to detect both of the two genotypes simultaneously. Two pairs of primers for nanoPCR were designed based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
(50 reference statements)
0
6
0
Order By: Relevance
“… 185 Authors reported the detection limit of 0.1 copies/µl and analyzed a total of 40 clinical samples, including 20 HPV‐positive and 20 HPV‐negative samples. Relatively large cohort of 209 cervical samples was used for validation of a novel nanoparticle‐assisted PCR assay (nanoPCR) for detection of E6 genes of HPV16 and HPV18 191 . Although authors did not calculate sensitivity and specificity of their nanoPCR assay, it displayed 10‐fold more sensitive detection than that of a conventional PCR, used only few microliters of the sample and allowed the reaction to reach more quickly the target temperature, hence shortening overall assay time.…”
Section: Nanomaterials Enhancing Assay Sensitivitymentioning
confidence: 99%
“… 185 Authors reported the detection limit of 0.1 copies/µl and analyzed a total of 40 clinical samples, including 20 HPV‐positive and 20 HPV‐negative samples. Relatively large cohort of 209 cervical samples was used for validation of a novel nanoparticle‐assisted PCR assay (nanoPCR) for detection of E6 genes of HPV16 and HPV18 191 . Although authors did not calculate sensitivity and specificity of their nanoPCR assay, it displayed 10‐fold more sensitive detection than that of a conventional PCR, used only few microliters of the sample and allowed the reaction to reach more quickly the target temperature, hence shortening overall assay time.…”
Section: Nanomaterials Enhancing Assay Sensitivitymentioning
confidence: 99%
“…Cervical cancer severely threatens women’s health and its incidence keeps growing at a very fast rate. Human papillomaviruses (HPVs), especially HPV type 18 (HPV-18), are important factors leading to cervical cancer [ 180 ]. Mahmoodi et al designed a rGO-MWNTs/ L -Cys-AuNPs nanocomposite through the modification of reduced graphene oxide (rGO), AuNPs, L -Cysteine ( L -Cys), and single strand DNA (ssDNA) probe to MWNTs as an electrochemical DNA-biosensor to diagnose HPV-18 [ 156 ].…”
Section: Carbon Nanotubes In Cancer Diagnosismentioning
confidence: 99%
“…Thus far, multiple studies have demonstrated the efficacy of nanoPCR. NanoPCR has been used to identify preclinical infections such as porcine parvovirus (PPV) [21], bovine respiratory syncytial virus (BRSV) [22], and human papillomavirus (HPV) [23]. However, to the best of our knowledge, the application of nanoPCR detection in GPV has not been used.…”
Section: Introductionmentioning
confidence: 99%